Estratégias de governo eletrônico e governança de TI: um estudo sobre a influência das estratégias de governo eletrônico em ações de governança de TI no governo do estado do Ceará - Freitas, Elidiane Martins (2014)
E-government is a strategy that uses the available resources of the Information Technology (IT) in government, aiming to better provide services/information to citizens, to improve their internal management and the interaction with partners and suppliers. The IT Governance has the main objective the alignment of their actions to set in a certain business strategies. Considering the strategic e-government to the Executive Power of the State of Ceará and IT Governance, a means by which IT support and extend this strategy, this study aimed to analyze the influence of e-government strategies in IT Governance Actions developed in the Government of the State of Ceará environment. Therefore, the study proposes specific objectives the analysis of e-government strategies and the analysis of existing IT Governance Actions in the agencies and entities that constitute the Executive Branch of the State of Ceará. This is a study of one case and incorporated in the analysis units are composed by EGovernment strategies and IT Governance actions of state agencies. The case study used three types of evidence, such as documents of eGovernment policies and IT Governance, published in the Official Gazette of the State; Questionnaires for the survey of e-government strategies and IT Governance actions, and; Semi-structured in-depth interviews. 32 policy documents were collected. It counted 52 agencies who answered the questionnaire. 18 interviews were held. The method of Qualitative content analysis was used for analysis of policy documents and interviews. To process the data from the questionnaires was used of descriptive statistics techniques. The insights gained with this case study indicate that the Influence of Electronic Government Strategies in IT Governance Actions occur through the observance of the policy documents related to the themes; and according to the complexity of Information Technology services provided by agencies.